Arab ESL secondary school students' spelling errors - Al-Sobhi, Bandar Mohammad Saeed; Md Rashid, Sabariah; Abdullah, Ain Nadzimah; Darmi, Ramiza (Australian International Academic Centre, 2017)
English spelling has always been described by many language researchers and teachers as a daunting task especially for learners whose first language is not English. Accordingly, Arab ESL learners commit serious errors when they spell out English words. The primary objective of this paper is to determine the types as well as the causes of spelling errors made by Arab ESL secondary school students. In order to collect the data, a fifty-word standardised spelling test was administered to seventy Arab student participants. The students’ types of spelling errors were detected, analysed and then categorised according to Cook’s (1999) classification of errors namely substitution, omission, insertion and transposition. In total, 2,873 spelling errors of various categories were identified. The study findings revealed that errors of substitution constituted the highest percentage of the students’ type of errors. In addition, the study indicated that the main causes of the students’ spelling errors were possibly attributed to the anomalous nature of the English spelling system, the Arab students’ lack of awareness of English spelling rules as well as L1 interference. Despite being conducted in an ESL context, the study was almost consistent with the findings indicated by other studies which were carried out in many Arabic EFL context. The findings suggest that spelling instruction should be emphasised while teaching English and should also be integrated with the skills and subskills of reading, writing, pronunciation and vocabulary in order to develop the students’ spelling accuracy.